Functional stability of a ferromagnetic polycrystalline Ni2MnGa high temperature shape memory alloy. (15th March 2017) - Azeem, M.A.; Jones, N.G.; Raghunathan, S.L.; Vorontsov, V.A.; Dye, D.
Abstract: Electrocaloric Ni2 MnGa is of interest for solid state refrigeration applications, as well as a high temperature thermal shape memory alloy. Here, polycrystalline Ni54 Mn25 Ga21 is examined using in situ synchrotron X-ray diffraction. The initial martensite ( M f ) and austenite ( A f ) finish temperatures were found to be 232 ° C and 298 ° C respectively. M f was observed to decline by 8 ° C/cycle and A f increased by 1 ° C/cycle. Both below and surprisingly, above the Curie temperature, the application of an e.m.f. was found to affect the lattice parameters measured. A change in the thermal expansion of the two phases was found around the Curie temperature. Graphical Abstract: